2015
DOI: 10.1080/09540105.2015.1104656
|View full text |Cite
|
Sign up to set email alerts
|

Determination of oxolinic acid residues in the muscle tissue of olive flounder (Paralichthysolivaceus) by a lateral flow immunoassay

Abstract: This study was designed to determine oxolinic acid (OA) residues in the muscle of olive flounder (Paralichthysolivaceus) by a lateral flow immunoassay (LFIA) and ultra-performance liquid chromatography coupled with fluorescence detection (UPLC-FLD). After 25 cultured olive flounder were treated by dipping in water dosed with OA (50 mg/L water for 1 h), muscle tissues were sampled and prepared for the detection of OA residues. The visual detection limit of the test strip for OA determined by the C/T ratio of 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…So far, the numbers of technologies have been established for OXO including high-performance liquid chromatography (HPLC), cyclic voltammetry (CV), spectrofluorometric, and so on. Although these technologies have excellent veracity, most of them are generally expensive and laborious, especially they are also time-consuming . These shortcomings have impeded their application in the routine detection of OXO.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the numbers of technologies have been established for OXO including high-performance liquid chromatography (HPLC), cyclic voltammetry (CV), spectrofluorometric, and so on. Although these technologies have excellent veracity, most of them are generally expensive and laborious, especially they are also time-consuming . These shortcomings have impeded their application in the routine detection of OXO.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, adverse reactions caused by antibiotics in the environment have become a problem of global concern. Tetracycline antibiotics are the most widely used antibiotics, commonly found in domestic sewage, medical wastewater, animal feed, and aquaculture wastewater discharge [1,2]. Research has been reported on eliminating antibiotics through membrane filtration, oxidation, photocatalysis, and biodegradation, which are costly, timeconsuming, and complex [3].…”
Section: Introductionmentioning
confidence: 99%
“…of quasi primary kinetic model and quasi secondary kinetic model for the adsorption of TCs by GO at different pH values.AdsorbatespH qe,exp (mg/g) Pseudo-Second-Order Pseudo-First-Order k2 q e (mg/g) R 2 k 1 q e (mg/g) R2 …”
mentioning
confidence: 99%